Antimicrobial stewardship programme in a trauma centre of a tertiary care hospital in North India: Effects and implementation challenges. (June 2019) - Verma, Madhur; Shafiq, Nusrat; Tripathy, Jaya Prasad; Nagaraja, Sharath Burugina; Kathirvel, Soundappan; Chouhan, Devendra Kumar; Arora, Pankaj; Singh, Tarundeep; Jain, Kajal; Gautam, Vikas; Dhillon, Mandeep Singh
Highlights: Implementation of an ASP in an Indian trauma centre and its effect on antimicrobial prescription were evaluated. A pre- and post-intervention study design was used to compare the effects of the ASP. The appropriateness of antimicrobial use increased during the intervention phase compared with the pre-intervention phase. Treatment based on susceptibility results increased, whilst prophylactic therapy decreased during the intervention phase. Many challenges to effective implementation of the ASP were encountered. Abstract: Objectives: Hospital-based antimicrobial stewardship programmes (ASPs) aim to optimise antimicrobial use by employing a set of co-ordinated interventions. This study evaluated the implementation challenges of an ASP in a tertiary trauma care centre in India and its effect on antimicrobial prescription. Methods: A pre- and post-intervention study design was used to compare the effects of the ASP amongst patients admitted during November 2017–January 2018. The appropriateness of antimicrobial prescriptions (dose, route, duration, indication, choice) was evaluated using a validated algorithm. ASP interventions involved daily audit and feedback, restriction on antibacterial usage, daily bedside review, education, and sensitisation activities for residents/nurses. Key implementation challenges and solutions were brainstormed in weekly meetings. Results: A total of 695 patients were prescribed 1331 antimicrobials. There was a decrease in prophylactic antimicrobial use by 11% ( P < 0.001). The prescription pattern improved significantly in the intervention phase compared with the pre-intervention phase in terms of duration, choice, indication and route of administration by 8%, 14%, 2% and 8% respectively. Patients in the intervention arm had significantly higher likelihood of receiving antimicrobials for an appropriate duration (aOR = 2.1, 95% CI 1.3–3.6; P = 0.004) and reason (aOR = 2.4, 95% CI 1.3–4.3; P = 0.003). Challenges identified in implementation included absence of an electronic recording system and inadequate orientation of treating doctors regarding rational antimicrobial use. Conclusions: The ASP demonstrated significant improvement in antimicrobial usage. This model may be replicated in other hospital settings to promote rational use of antimicrobials.